Pemberdayaan Masyarakat Melalui Distribusi Zakat Produktif Baznas Provinsi Kalimantan Barat - Dwi Fajar Ramadhoni; Zaenuddin; Ichsan Iqbal (Masyarakat Ekonomi Syariah Bogor, 2025)
This research explores the role and impact of productive zakat distribution by the National Zakat Board (Baznas) of West Kalimantan Province in empowering local communities. Using a qualitative-descriptive method, this study investigates the forms, implementation factors, and outcomes of community empowerment programs driven by productive zakat mechanisms. Findings reveal that productive zakat not only provides financial assistance to the needy but also serves as a strategic instrument for sustainable economic development. By enabling mustahik to initiate micro-enterprises, Baznas has facilitated income growth, financial independence, and a gradual transition from mustahik to muzakki. However, challenges such as limited financial literacy, weak institutional support, and inconsistent program monitoring remain. This study recommends enhanced training, collaborative governance, and systematic impact assessment to optimize the effectiveness of productive zakat. The implications highlight zakat's potential as a transformative tool in Islamic social finance and poverty alleviation within the Indonesian socio-economic context.